Treatment with a New Peroxisome Proliferator-Activated Receptor Gamma Agonist, Pyridinecarboxylic Acid Derivative, Increases Angiogenesis and Reduces Inflammatory Mediators in the Heart of Trypanosoma cruzi-Infected Mice - Penas, Federico Nicolás; Carta, Davide; Dmytrenko, Ganna; Mirkin, Gerado A.; Modenutti, Carlos Pablo; Cevey, Ágata Carolina; Rada, Maria Jimena; Ferlin, Maria Grazia; Sales, María Elena; Goren, Nora Beatriz (Frontiers in Immunology, 2017)
Trypanosoma cruzi infection induces an intense inflammatory response in diverse host tissues. The immune response and the microvascular abnormalities associated with infection are crucial aspects in the generation of heart damage in Chagas disease. Upon parasite uptake, macrophages, which are involved in the clearance of infection, increase inflammatory mediators, leading to parasite killing. The exacerbation of the inflammatory response may lead to tissue damage. PPARγ is a ligand-dependent nuclear transcription factor that exerts important anti-inflammatory effects and is involved in improving endothelial functions and proangiogenic capacities. In this study we evaluated the intermolecular interaction between PPARγ and HP24 using virtual molecular docking. Also, we showed that early treatment with a new PPARγ synthetic ligand, HP24, decreases the expression of NOS2, a proinflammatory mediator, and stimulates proangiogenic mediators (VEGF-A, CD31, Arginase I) both in macrophages and in the heart of T. cruzi-infected mice. Moreover, HP24 reduces the inflammatory response, cardiac fibrosis and the levels of inflammatory cytokines (TNF-α, IL-6) released by macrophages of T. cruzi-infected mice. We consider that PPARγ agonists might be useful as coadjuvants of the anti-parasitic treatment of Chagas disease, to delay, reverse, or preclude the onset of heart damage.